(untitled) (American Journal of Technology and Applied Sciences, 2023)
The interoperability of Intelligent Electronic Devices (IEDs) supplied by various businesses during the growth is currently a challenge for electric power providers. A current electrical substation. Recently, an effort has been undertaken to create a global standard to solve the interoperability issue. For flexible data transmission across IEDs in an electric power substation, the European standard "International Electro-technical Commission (IEC) 61850" is gaining acceptance globally. To enable interoperability amongst the various equipment, this article describes a hypothetical substation automation scheme in accordance with the IEC-61850 standard.